2014
DOI: 10.1177/0883073814523318
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Subependymal Giant Cell Astrocytomas Associated With Tuberous Sclerosis Complex

Abstract: Tuberous sclerosis complex is a genetic disorder characterized by benign tumor growth including lesions in the ventricular system of the brain known as subependymal giant cell astrocytomas. This analysis focuses on the clinical presentation, management, and associated burden of subependymal giant cell astrocytomas in patients with tuberous sclerosis complex in the United States. An institutional review board-approved web-based survey of tuberous sclerosis complex patients and caregivers collected information, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…However, the TSC guidelines indicate that more surveillance activities (including those studied) should have been recorded in order to monitor symptom progression 1,23 and optimize patient care; it is, thus, concerning that half of the patients recorded no procedures, and one in five patients reported no diagnostic tests. This neglect may contribute to the development of preventable catastrophic events later in life such as kidney failure or death due to uncontrolled epilepsy 40,41 . Furthermore, as morbidity and mortality are most pervasive in adults and associated with later onset pulmonary and renal manifestations 42,43 , we can expect disease complexity and associated healthcare resource use to increase with age.…”
Section: Discussionmentioning
confidence: 99%
“…However, the TSC guidelines indicate that more surveillance activities (including those studied) should have been recorded in order to monitor symptom progression 1,23 and optimize patient care; it is, thus, concerning that half of the patients recorded no procedures, and one in five patients reported no diagnostic tests. This neglect may contribute to the development of preventable catastrophic events later in life such as kidney failure or death due to uncontrolled epilepsy 40,41 . Furthermore, as morbidity and mortality are most pervasive in adults and associated with later onset pulmonary and renal manifestations 42,43 , we can expect disease complexity and associated healthcare resource use to increase with age.…”
Section: Discussionmentioning
confidence: 99%
“…The measures of DALY and QALY were only used by one study that calculated projected costs of different treatment strategies for epilepsy in TSC [109]. Fourteen studies reported on quality of life [53,56,101,103,105,106,108,115,118,119,[121][122][123]125]. Nine studies (also) reported BOI for caregivers [56,102,105,106,108,115,117,119,125] (five studies reported analyses of the same population or subgroups of the same).…”
Section: Burden Of Illness and Resource Usementioning
confidence: 99%
“…In this study, more than two-thirds of patients worked for pay, but the type (primary vs. subsidized labor market) was not stated by the authors. TSC patients had substantial yearly out-of-pocket costs (median of USD 1750 for pediatric and median of USD 3270 for adult patients, respectively) for both outpatient and hospital care in a US cohort [106]. In a study on BOI of facial angiofibromas in a US population, the cost of medication and lack of a suitable pharmacy were seen as biggest hurdles in receiving topical rapamycin therapy [108], but average costs were not given.…”
Section: Direct Costsmentioning
confidence: 99%
“…Central nervous system manifestations are a common source of morbidity, e.g. infantile spasms [ 14 ], seizures, intellectual disability, and neoplasms (giant-cell astrocytoma) [ 17 ], [ 29 ]. Epilepsy is very frequently, though not invariably, diagnosed in TSC affected individuals [ 24 ], [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…infantile spasms [ 14 ], seizures, intellectual disability, and neoplasms (giant-cell astrocytoma) [ 17 ], [ 29 ]. Epilepsy is very frequently, though not invariably, diagnosed in TSC affected individuals [ 24 ], [ 29 ]. Common causes of mortality are pulmonary lymphangioleiomyomatosis, kidney angiomyolipomas, and cardiac rhabdomyoma [ 5 ], [ 27 ], [ 34 ].…”
Section: Introductionmentioning
confidence: 99%